2023
DOI: 10.1177/11769351231171743
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of MicroRNA Expression Data in Liver Cancer

Abstract: Abnormal miRNA expression has been evidenced to be directly linked to HCC initiation and progression. This study was designed to detect possible prognostic, diagnostic, and/or therapeutic miRNAs for HCC using computational analysis of miRNAs expression. Methods: miRNA expression datasets meta-analysis was performed using the YM500v2 server to compare miRNA expression in normal and cancerous liver tissues. The most significant differentially regulated miRNAs in our study undergone target gene analysis using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 126 publications
0
0
0
Order By: Relevance
“…This method enables simulation and analysis of biological processes, predicting protein structures, and understanding gene interactions without expensive and time-consuming laboratory experiments [25][26][27][28]. Previous studies have demonstrated the feasibility of in-silico analysis in identifying potential interactions of genes, pathways, or cellular mechanisms, offering valuable clues for further experimental validation [21,26,[28][29][30][31][32][33][34]. Hence, the objective of this study is to utilize in-silico analysis to investigate the role of the TBX1 gene within the context of 22q11.2 deletion syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…This method enables simulation and analysis of biological processes, predicting protein structures, and understanding gene interactions without expensive and time-consuming laboratory experiments [25][26][27][28]. Previous studies have demonstrated the feasibility of in-silico analysis in identifying potential interactions of genes, pathways, or cellular mechanisms, offering valuable clues for further experimental validation [21,26,[28][29][30][31][32][33][34]. Hence, the objective of this study is to utilize in-silico analysis to investigate the role of the TBX1 gene within the context of 22q11.2 deletion syndrome.…”
Section: Introductionmentioning
confidence: 99%